Multipolar pulsed-field ablation for the treatment of left atrial reentry tachycardia. (19th May 2022) - Kueffer, T; Seiler, J; Madaffari, A; Muehl, A; Noti, F; Haeberlin, A; Servatius, H; Tanner, H; Baldinger, S; Reichlin, T; Roten, L
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: A multipolar pulsed field ablation (PFA) catheter was recently introduced for pulmonary vein isolation and combines the benefits of high procedural efficacy and safety. It may also be used to treat left atrial (LA) reentry tachycardia. Purpose: To describe our initial experience using a multipolar PFA catheter for the treatment of LA reentry tachycardia. Methods: We included all patients with LA reentry tachycardia treated with a multipolar PFA catheter at our institution. Using 3D electro-anatomical mapping (3D-EAM), we identified the tachycardia mechanism and applied linear lesions either at the left atrial roof, mitral isthmus or on the anterior wall, as appropriate. Positioning of the PFA catheter was verified by integration into 3D-EAM. Applications were performed using 2.0kV with the catheter in basket or flower configuration, depending on ablation site. Bidirectional block across linear lesions was verified using standard criteria. Additional focal radiofrequency ablation (RFA) was used to achieve bidirectional block if necessary. Results: We treated 17 LA reentry tachycardia with a multipolar PFA catheter in 13 patients (median age 69 (59-73) years; 5 females). The tachycardia mechanism was identified as roof-dependent in five, peri-mitral in eight and anterior scar-related in four cases. PFA lesion sets consisted of 12 posterior wall isolations (i.e. roof lines), four mitral isthmus lines (MIL) and eight anterior lines. For ablation of the mitral side of the anterior line, we always used the PFA catheter in basket configuration, while we targeted the posterior wall and the superior side of the anterior line exclusively with the catheter in flower configuration. To ablate the MIL we used both flower and basket configurations. Three roof-dependent, six peri-mitral, and four anterior scar-related tachycardias were successfully terminated by PFA (76%). Additional RFA was necessary for two MIL, two anterior lines and no roof line (17%). Finally, we achieved bidirectional block across all lines. PFA triggered, vagal-mediated and reversible AV block was observed in one case. Otherwise, there were no acute procedural complications. Conclusion: Linear lesion sets are feasible and safe using a multipolar PFA catheter. Posterior wall isolation by PFA for the treatment of roof-dependent LA reentry tachycardia is highly efficient while anterior lines and MIL remain challenging and may need complementary RFA or a PFA catheter designed for focal or linear ablations.